Hubungan antara Self Efficacy dengan Flow Akademik pada Siswa Akselerasi SMPN 1 Sidoarjo - Eni Purwati; Mashubatul Akmaliyah (Psympathic : Jurnal Ilmiah Psikologi, 2016)
Academic Flow is a condition where person feel comfortable, able to concentrate, has inner motivation, and also able to enjoy doing academic activity. Self efficacy is believe inside someone has the ability to decide correct behavior to achieve desired success. Purpose of this research is to know the correlation between self efficacy and academic flow on student acceleration. Self efficacy is acknowledged as the trigger which pushes someone learning activity until they had flow condition. This research is correlational quantitative with a subject 24 acceleration students. The result of the study showed correlation between self efficacy and academic flow on acceleration students positive linear, which is mean the higher self efficacy the higher academic flow. High self efficacy able to control the behavior to maintain the effort to do the assignment which make easy to reach the academic flow.